School Principals’ Stressors and Coping Strategies : A Comparative Study Between Finland and Canada - Bodson, Claudine (2021)
The aim of this study was to investigate the stressors and coping strategies of school principals in Finland and Canada with the help of three research questions: what are the causes of the job stressors?, what strategies do school principals use to try to cope with these stressors?, and what specific support do school principals need, or what changes should occur to support them? Using the results of this qualitative study, the main job stressors, coping strategies, and support mechanisms were identified. The research data included both the diaries (N=8) and individual interviews (N=8) of principals. Regarding the analysis, after the theory-guided phase focusing on the diaries, the data-based phase focused on both diaries and interviews. The research findings showed that the main stressors in both Finland and Canada were workload and insufficient time to complete tasks, and constant interruptions. Canadian principals worked significantly more than their Finnish counterparts. School violence and disagreements also caused job stress for principals. In Finland, only verbal disagreements were reported, not physical violence, except for one case of bullying. With regards to coping strategies, the data showed that principals took care of their physical and mental health through a variety of activities. They also knew how to prioritize and were proactive in many cases. Finnish principals frequently delegated work, an uncommon practice in Canada. Regarding support, the lack or non-replacement of human resources seemed to be a major issue in both countries. Nevertheless, the data showed that in both countries, principals were well supported by the network of people around them. Keywords: School principal, stressor, coping strategy, support, comparative study